MYC-mediated Synthetic Lethality for Treatment of Hematological Malignancies - Li, Xin; A. Zhang, Xin; Xie, Wei; Li, Xiaoqing; Huang, Shiang (Current Cancer Drug Targets, 2015)
Deregulated c-MYC expression is found in many human malignancies. MYC activation induces multiple lineages of hematological malignancies in single Myc transgenic mice. MYC inactivation causes tumor regression. MYC is therefore an attractive target for cancer treatment. However, little progress has been made in the development and application of targeted MYC inactivation in clinical practice. In double Myc transgenic mouse models, Myc-driven leukemogenesis and lymphomagenesis can be accelerated by transduction of non-MYC oncogenes, leading to dual addiction to MYC and the non-MYC oncogenes. Wang et al. (2004) first established the concept of MYC-mediated synthetic lethality (MYC-SL). MYC overexpression sensitized cells to TRAILand DR5-agonist-induced apoptosis. This suggests that MYC-dependent tumor cells may be killed by targeting partner oncogenes of MYC. Many small molecule inhibitors (SMIs) have been proven to induce MYC-SL by targeting AUK-B, Brd4, CDK1, CHK1, MCL-1, the mTOR/4E-BP1/eIF4E pathway, and PIM1/2. Compared with conventional treatment approaches, SMI-induced MYC-SL displays highly selective anticancer activity and much lower cytotoxicity to normal cells. SMI-induced MYC-SL can reverse eIF4F- and PIM2-induced multiple chemoresistance. The combination of an SMI with chemotherapeutic agents can elevate chemotherapy efficacy by enhancing chemosensitivity. This combination will be a promising novel approach to treating MYC-dependent tumors by inducing MYC-SL.
Keywords: tumorigenesis